2006
DOI: 10.1291/hypres.29.65
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Reduction of Systemic Arterial Compliance Induces Excessive Myocardial Oxygen Consumption during Sub-Maximal Exercise

Abstract: Reduction of systemic arterial compliance (SAC) with aging increases left ventricular afterload. The present study was designed to examine whether age-related reduction of SAC is related to excessive myocardial oxygen consumption during sub-maximal aerobic exercise. We studied elderly (60-69 years; n =25) and senior (70-82 years; n =25) subjects. We measured SAC immediately before the start of the ramp-fashion exercise (i.e., at the end of the 20 W warm-up exercise) and the double product (DP: systolic blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…A decreased central arterial distensibility results in an (22,26). It has been reported that acute exercise induces an increase in arterial distensibility in young humans (14,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A decreased central arterial distensibility results in an (22,26). It has been reported that acute exercise induces an increase in arterial distensibility in young humans (14,27).…”
Section: Discussionmentioning
confidence: 99%
“…A carotid arterial waveform has been used as the central arterial waveform to esti- mate SAC non-invasively (10). In the present study, a finger arterial waveform was transformed to a brachial arterial waveform using analysis software (Beatscope; TNO-BMI, Amsterdam, the Netherlands) (20,21); the transformed arterial waveform was used to calculate SAC instead of the carotid arterial waveform (22,23). We estimated SV using the Modelflow method from the transformed arterial waveform using Beatscope (24,25).…”
Section: Measurement Of Sacmentioning
confidence: 99%
“…Again, we demonstrated a linear relationship between carotid arterial PWV and cardiovagal BRS. It is well-established that arterial stiffness increases with advancing age (Avolio et al, 1985;Otsuki et al, 2006a;Otsuki et al, 2006b;Vaitkevicius et al, 1993). Central arterial stiffness are also associated with daily physical activities (Iemitsu et al, 2006;Sugawara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Takeshi OTSUKI 1) , Seiji MAEDA 1), 2) , Jun SUGAWARA 3) , Yumiko KESEN 2) , Haruka MURAKAMI 4) , Takumi TANABE 1) , Takashi MIYAUCHI 1), 5) , Shinya KUNO 2) , Ryuichi AJISAKA 2) , and Mitsuo MATSUDA 1) A decrease in systemic arterial compliance (SAC) increases left ventricular load along with the demand for excessive myocardial oxygen consumption when the age-related reduction of SAC reaches a marked level, and consequently may depress left ventricular pump function. Reduced left ventricular pump function decreases aerobic capacity, and some study groups have shown that SAC and/or central arterial distensibility is correlated with maximal aerobic capacity in humans.…”
Section: Age-related Reduction Of Systemic Arterial Compliance Relatementioning
confidence: 99%
“…, double product: SBP × heart rate) during sub-maximal aerobic exercise (5). However, the relationship of arterial compliance and double product remains not significant until the reduction of arterial compliance reaches a marked level (5).…”
Section: Introductionmentioning
confidence: 99%